The Future of Logistics in Emerging Markets – Fuzzy Clustering Scenarios Grounded in Institutional and Factor-Market Rivalry Theory - Hirschinger, Micha; Spickermann, Alexander; Hartmann, Evi; von der Gracht, Heiko; Darkow, Inga-Lena (Journal of Supply Chain Management, 2015)
Transportation and logistics are increasingly relevant to the rapid economic growth of emerging economies. Decision makers in the transportation and logistics industry require a comprehensive understanding of the institutional business environment and factor markets in emerging economy countries to formulate accurate supply chain strategies for the future. Although extensive studies on prospective scenarios in emerging economies are available, research has largely neglected the future evolution of transportation and logistics. This study addresses this gap by applying a multiple method research approach and relying on institutional theory and factor-market rivalry theory to create scenarios of the development of transportation and logistics in emerging economy countries by 2030. We do so by collecting qualitative and quantitative data through a Delphi survey and applying fuzzy clustering to group the results into meaningful and interpretable scenarios. Our results suggest that emerging economies will take advantage of free trade zones to consolidate their position in the international market and encourage investment. Consequently, logistics will experience rapid growth and value-added services will expand, propelling new players from developing economies onto the international stage. Our findings also suggest that the logistics service industry in emerging economy countries will undergo a significant consolidation process, leading to the possibility of factor-market rivalry among shippers. This suggests that shippers' social networks and personal contacts will increase in importance in the futur
Keywords: Transportation; Distribution; Logistics; Emerging; Economies; Institutional; Theory; Factor-market; Rivalry; Theory; Panel; Study; Fuzzy; Logic; Cluster; Analysis